OBSERVATIONS OF APOPHIS IN NSFCTC (YEVPATORIA) AND RI NAO (MYKOLAIV) - Kozhukhov, A. M.; Maigurova, N. V.; Pomazan, A. V.; Kryuchkovskiy, V. F. (Одеські астрономічні публікації, 2013)
The results of observations of potentially hazardous asteroid Apophis, performed in January-February 2013 are presented. Technical characteristics of equipment and method of observation are described. The results are shown in comparison with the observations of this object by other observatories.